Finding Missing Interactions of the Arabidopsis thaliana Root Stem Cell Niche Gene Regulatory Network - Azpeitia, Eugenio; Weinstein, Nathan; Benítez, Mariana; Mendoza, Luis; Alvarez-Buylla, Elena R. (Frontiers in Plant Science, 2013)
Abstract Over the last few decades, the Arabidopsis thaliana root stem cell niche has become a model system for the study of plant development and the stem cell niche. Currently, many of the molecular mechanisms involved in root stem cell niche maintenance and development have been described. A few years ago, we published a gene regulatory network model integrating this information. This model suggested that there were missing components or interactions. Upon updating the model, the observed stable gene configurations of the root stem cell niche could not be recovered, indicating that there are additional missing components or interactions in the model. In fact, due to the lack of experimental data, gene regulatory networks inferred from published data are usually incomplete. However, predicting the location and nature of the missing data is a not trivial task. Here, we propose a set of procedures for detecting and predicting missing interactions in Boolean networks. We used these procedures to predict putative missing interactions in the A. thaliana root stem cell niche network model. Using our approach, we identified three necessary interactions to recover the reported gene activation configurations that have been experimentally uncovered for the different cell types within the root stem cell niche: 1) a regulation of PHABULOSA to restrict its expression domain to the vascular cells, 2) a self-regulation of WOX5, possibly by an indirect mechanism through the auxin signalling pathway and 3) a positive regulation of JACKDAW by MAGPIE. The procedures proposed here greatly reduce the number of possible Boolean functions that are biologically meaningful and experimentally testable and that do not contradict previous data. We believe that these procedures can be used on any Boolean network. However, because the procedures were designed for the specific case of the root stem cell niche, formal demonstrations of the procedures should be shown in future efforts.